Az interaktív mesekönyv medialitása - Varga, Emőke (Studia Litteraria, 2019)
The study will discuss the definitive, disciplinary and medial aspects of the interactive story book, which is a genre having only a few years of history. The question about the correlation of lingual and image mediums, based on theories that present a formal link between still images and written word by the text-image researches, is described with the category of inter-references. In both cases the text and its illustration – the motion picture and the voice - are detached, the receiver is able to separate these media explicitly while experiencing their coherence at the same time. In interactive story books, to compare with traditional picture-books, the inter-references are multiplied, because in these mobile applications the written and vocal modus of lingual medium are cooperating with the still and moving modus of the image illustration. Through the adaptation of The Little Red Riding Hood and other international and Hungarian applications the study discusses how these relationships are created in three correlating layers, and in a fourth one, in the sub-classic layer and also models the two extreme poles of the semantic relationships of the media.